Economic Impact of Metabolic Dysfunction-Associated Steatotic Liver Disease (MASLD) in Italy. Analysis and Perspectives - Torre E; Di Matteo S; Martinotti C; Bruno GM; Goglia U; Testino G; Rebora A; Bottaro LC; Colombo GL (Dove Medical Press, 2024)
Enrico Torre,1 Sergio Di Matteo,2 Chiara Martinotti,2 Giacomo Matteo Bruno,3 Umberto Goglia,4 Gianni Testino,5 Alberto Rebora,1 Luigi Carlo Bottaro,6 Giorgio Lorenzo Colombo3 1Diabetology and Metabolic Diseases Unit - ASL3, Genoa, Italy; 2Center of Research, SAVE Studi - Health Economics and Outcomes Research, Milan, Italy; 3Department of Drug Sciences, University of Pavia, Pavia, Italy; 4Territorial Diabetology Unit, ASLCN1, Cuneo, Italy; 5Units of Addiction and Hepatology, ASL3, Genoa, Italy; 6General Direction, ASL3, Genoa, ItalyCorrespondence: Giorgio Lorenzo Colombo, Email giorgio.colombo@unipv.itBackground: Metabolic dysfunction-associated steatotic liver disease (MASLD) is a multisystem condition destined to become pandemic in the coming decades. This study aimed at evaluating the economic impact of MASLD in the Italian population from the Italian National Healthcare Service (NHS) perspective.Methods: The economic impact of the MASLD was assessed by developing a calculation model in Microsoft Excel® from the Italian NHS perspective, considering healthcare resources and direct costs. The target population was based on the prevalence data. Through a literature search, complications of MASLD were identified, including MASH, with relative risk of evolution into CC, DCC, HCC, T2DM, cardiovascular diseases, in particular AMI and stroke, CKD, and CRC. The differential impact between complication development in the population with MASLD and the same sample size population without-MASLD was evaluated. Differential risk data, mortality rates, and event unit costs were drawn from the published international literature. Frequency and cost data were applied to the total target population, the total annual costs and mortality data, referring to the two arms, were then calculated, and the differential value was obtained.Results: Based on an estimated 11,546,370 MASLD target population, an annual illness impact of € 12,251,631,822 was calculated, corresponding to a difference of € 7,731,674,054 compared with the same sample size without MASLD. Moreover, the MASLD population is expected to experience 13,438 additional deaths annually.Conclusion: The growing epidemiological impact of MASLD and its complications represent a huge economic burden for healthcare services worldwide. An integrated approach, including changes in lifestyle behaviors, will be the first step. Specific drugs for MASLD are not yet available; however, studies are underway, and combined pharmaceutical therapies may be an inevitable choice to achieve adequate control of MASLD and its complications.Keywords: metabolic associated fatty liver disease MASLD, complications, MASLD burden in Italy, healthcare costs, treatment and perspectives